A cross-cultural religiology between reductionism and anti-reductionism - Wang, Guicai (HTS teologiese studies, 2023)
‘Religion’ has been subjected to two kinds of reduction: one from the various branches of religious studies, the other being the mutual ‘reduction’ among religions. We advocate a cross-cultural religiology and try to take a middle path between reductionism and anti-reductionism, responding to both kinds of reduction separately. As for the former reduction, we agree with a moderate reduction of religion by various religious disciplines on the one hand, and on the other hand, we propose to respect the religious whole as an integrate human activity, and try to learn to face and study religion with a holistic attitude and method. For the latter reduction, we propose three points to overcome the merely reductive cognitive approach in inter-religious understanding without falling into some kind of anti-intellectualism. Firstly, we insist that we should face the other religions with a pluralistic confidence without giving up understanding, and engage both ‘dialogical dialogue’ and ‘dialectical dialogue’ with other religions. Secondly, we advocate learning from the wisdom of Buddha, Confucius and Jesus, giving priority to practice, and being concerned about our most urgent life practice of the moment. Thirdly, we propose that cross-cultural research can be carried out thematically, which is exemplified with the author’s cross-cultural research on ‘the other shore’.Contribution: In the field of religious studies, there is constant dispute between reductionism and anti-reductionism. This article tries to place cross-cultural religiology between reductionism and anti-reductionism, avoid the debate between the two, emphasise the integrity of religion as a whole human activity, and propose some practical and usable methods for cross-cultural religiology, hoping to have some inspiration for academic colleagues.